Elective Affinities - Le affinità elettive - Paolo Taviani, Vittorio Taviani (1996)
Early in the 19th century, Edward and Carlotta, in love 20 years ago, find each other and marry. After a year's bliss at his Tuscan villa, Edward begs to invite Otto, an architect and friend, to join them. She has forebodings of disaster, but relents. Otto arrives, and to balance the dynamics, Carlotta invites her teenage godchild Ottilia to join them. Ottilia stirs Edward, Otto and Carlotta are attracted to each other, and these longings produce in Edward and Carlotta a night of passion that results in pregnancy. Otto leaves for Venice, Edward leaves for war, and a baby looking like Otto and Ottilia is born. Can anything be put right? Can the four return to their initial happiness?
Keywords: Comedy, Drama, Romance